Bundling gender responsive socio-technical innovations: Unpacking the what and how - Nchanji, Eileen Bogweh; Lutomia, Cosmas Kweyu; Ketema, Dessalegn Molla; Mapedza, Everisto D.; Gartaula, Hom Nath; Mukhopadhyay, Prama; Puskur, Ranjitha; Johnstone, Kevin; Barrett, Sam (2023)
The CGIAR Gender Equality Initiative organized a stakeholder workshop on 23 – 24 May 2023. The workshop focused on exploring the technology and innovation bundles that have the potential to revolutionize farming practices and enhance the resilience of women farmers. The workshop officially opened by Dr Nicoline de Haan, Director, CGIAR Gender Impact Platform, served as a forum for diverse stakeholders, including researchers, policymakers, farmers, and industry representatives, to collaborate and envision transformative solutions that address the specific technological needs and challenges women farmers face.